Productivity of cassava intercrop as influenced by cassava variety and time of introducingrice into cassava - Jalloh, A.; Dahniya, Mohamed T.; Ezumah, H.C. (1994)
The study was carried out to determine the most appropriate time of introducing rice into cassava with the aim of improving the total productivity of the intercrop. The rice variety Rok 16 was introduced into cassava at four different times—planted at the same time with cassava, and then at 2, 4, and 6 wk after cassava. The cassava varieties used were 80/40, an improved clone, and the local Cocoa. Both variety and time of introducing rice into cassava affected tuberous root yield of cassava. Variety 80/40 significantly out yielded Cocoa, while cassava tuberous root yield significantly increased the later rice was introduced into cassava. Rice grain yield significantly decreased as planting was delayed. At each planting date sole rice yield was significantly higher than that of intercropped rice which did not vary with cassava variety. Land equivalent ratio (LER) increased as the time of introducing rice into cassava was delayed. Results of the study indicate that for improved productivity of the system, rice should be introduced between 4 and 6 wk after planting cassava and that growing rice with the improved variety 80/40 resulted in higher productivity than with Cocoa.